Effects of blank dimension on forming characteristics during conical-section ring rolling of Inco718 alloy. Issue 9 (June 2016) - Zhu, Xinglin; Liu, Dong; Yang, Yanhui; Hu, Yang; Liu, Guowei; Wang, Yuanning
Abstract For profile ring rolling of difficult-to-deform materials, geometry and dimensions of blank are critical for dimensional accuracy and thermomechanical parameters distribution of the formed ring. In this study, four blank design principles for conical-section ring rolling are presented based on analytical description of the volume distribution characteristic curve (VDCC), and then effects of all dimension factors of the four blanks are explored comprehensively by using 3D coupled thermomechanical FE model established based on FORGE. According to the comprehensive analysis, optimal blank design principle for conical-section ring rolling is determined. The results obtained show that: (1) Preparation stage of rolling process (PSRP) is an essential stage for slope forming without wall thickness reduction, and the essence of PSRP is the process that the metal in rolling cavity seeking for balanced pressure along axial direction. (2) Unequal slope and unequal wall thickness have obvious effects on stress distribution. (3) We can, through controlling local deformation in PSRP and shortening the time of PSRP, improve the strain and the temperature distribution.